The effectiveness of Quizizz media to improve learning outcomes on income inequality - Aghnia Rachmawati; Larisa Saputri; Ari Kusmiatun; Rinawati Rinawati (COPE: Caraka Olah Pikir Edukatif, 2026)
Learning motivation plays an important role in determining the success of economic learning, especially on the topic of income inequality, which is often considered abstract and difficult for students to understand. Learning evaluations using conventional methods tend to decrease students’ interest and engagement, resulting in less optimal learning outcomes. Therefore, the use of gamification-based digital media such as Quizizz is seen as an alternative that can increase both motivation and learning outcomes. This study aims to determine the effectiveness of using Quizizz as an evaluation medium in economics learning on the topic of income inequality, as well as to analyze the benefits and challenges of its implementation. The method used is qualitative descriptive, involving 36 students of class XI F1.3 at SMA Negeri 1 Turi as research subjects. Data was collected through observation and documentation of evaluation results using Quizizz, and then analyzed through the stages of reduction, presentation, and drawing conclusions. The study results indicate that Quizizz is capable of increasing both intrinsic and extrinsic learning motivation, as reflected in the improvement of average evaluation scores of 82% and 79%. Furthermore, this media creates a more interactive learning atmosphere, encourages healthy competition, and provides immediate feedback that helps students improve their understanding. Teachers also benefit from the convenience, as Quizizz presents evaluation results in a detailed and structured manner. Challenges encountered include device limitations and varying internet quality among students. Overall, Quizizz is effective as a digital evaluation medium and can be used as an innovative alternative in teaching economics as well as other subjects